Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's solve each part step-by-step.
### Part (a) [tex]$\log _8 5-\log _8 11=\log _8 \square$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b(a) - \log_b(b) = \log_b \left(\frac{a}{b}\right) \][/tex]
Here, [tex]\(a = 5\)[/tex] and [tex]\(b = 11\)[/tex], so:
[tex]\[ \log_8 5 - \log_8 11 = \log_8 \left(\frac{5}{11}\right) \][/tex]
Therefore, the missing value is:
[tex]\[ \square = \frac{5}{11} \][/tex]
So, [tex]\(\log_8 5 - \log_8 11 = \log_8 \left(\frac{5}{11}\right) \)[/tex].
### Part (b) [tex]$\log _7 \square+\log _7 11=\log _7 33$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b(a) + \log_b(b) = \log_b (a \cdot b) \][/tex]
Here, [tex]\(b = 11\)[/tex] and the product is [tex]\(33\)[/tex]. We need to find [tex]\(a\)[/tex]:
We know that:
[tex]\[ \log_7 (a) + \log_7 (11) = \log_7 (33) \][/tex]
So, the value of [tex]\(a\)[/tex] must be:
[tex]\[ a \cdot 11 = 33 \][/tex]
[tex]\[ a = \frac{33}{11} \][/tex]
[tex]\[ a = 3 \][/tex]
Therefore, the missing value is:
[tex]\[ \square = 3 \][/tex]
So, [tex]\(\log_7 3 + \log_7 11 = \log_7 33 \)[/tex].
### Part (c) [tex]$\log _7 \frac{1}{25} = -2 \log _7 \square$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b \left(\frac{1}{a^2}\right) = -2 \log_b (a) \][/tex]
Here, the left-hand side is:
[tex]\[ \log_7 \left(\frac{1}{25}\right) \][/tex]
We need to find the value of [tex]\(a\)[/tex] such that:
[tex]\[ \log_7 \left(\frac{1}{25}\right) = -2 \log_7 (a) \][/tex]
We know that:
[tex]\[ \frac{1}{25} = \frac{1}{5^2} = 5^{-2} \][/tex]
So, we have:
[tex]\[ \log_7 \left(5^{-2}\right) = -2 \log_7 (5) \][/tex]
Therefore, the missing value is:
[tex]\[ \square = 5 \][/tex]
So, [tex]\(\log_7 \frac{1}{25} = -2 \log_7 5 \)[/tex].
### Summary of the Solutions:
(a) [tex]\(\log _8 5-\log _8 11=\log _8 \left(\frac{5}{11}\right)\)[/tex]
(b) [tex]\(\log _7 3+\log _7 11=\log _7 33\)[/tex]
(c) [tex]\(\log _7 \frac{1}{25}=-2 \log _7 5\)[/tex]
### Part (a) [tex]$\log _8 5-\log _8 11=\log _8 \square$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b(a) - \log_b(b) = \log_b \left(\frac{a}{b}\right) \][/tex]
Here, [tex]\(a = 5\)[/tex] and [tex]\(b = 11\)[/tex], so:
[tex]\[ \log_8 5 - \log_8 11 = \log_8 \left(\frac{5}{11}\right) \][/tex]
Therefore, the missing value is:
[tex]\[ \square = \frac{5}{11} \][/tex]
So, [tex]\(\log_8 5 - \log_8 11 = \log_8 \left(\frac{5}{11}\right) \)[/tex].
### Part (b) [tex]$\log _7 \square+\log _7 11=\log _7 33$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b(a) + \log_b(b) = \log_b (a \cdot b) \][/tex]
Here, [tex]\(b = 11\)[/tex] and the product is [tex]\(33\)[/tex]. We need to find [tex]\(a\)[/tex]:
We know that:
[tex]\[ \log_7 (a) + \log_7 (11) = \log_7 (33) \][/tex]
So, the value of [tex]\(a\)[/tex] must be:
[tex]\[ a \cdot 11 = 33 \][/tex]
[tex]\[ a = \frac{33}{11} \][/tex]
[tex]\[ a = 3 \][/tex]
Therefore, the missing value is:
[tex]\[ \square = 3 \][/tex]
So, [tex]\(\log_7 3 + \log_7 11 = \log_7 33 \)[/tex].
### Part (c) [tex]$\log _7 \frac{1}{25} = -2 \log _7 \square$[/tex]
To solve this, we will use the property of logarithms that states:
[tex]\[ \log_b \left(\frac{1}{a^2}\right) = -2 \log_b (a) \][/tex]
Here, the left-hand side is:
[tex]\[ \log_7 \left(\frac{1}{25}\right) \][/tex]
We need to find the value of [tex]\(a\)[/tex] such that:
[tex]\[ \log_7 \left(\frac{1}{25}\right) = -2 \log_7 (a) \][/tex]
We know that:
[tex]\[ \frac{1}{25} = \frac{1}{5^2} = 5^{-2} \][/tex]
So, we have:
[tex]\[ \log_7 \left(5^{-2}\right) = -2 \log_7 (5) \][/tex]
Therefore, the missing value is:
[tex]\[ \square = 5 \][/tex]
So, [tex]\(\log_7 \frac{1}{25} = -2 \log_7 5 \)[/tex].
### Summary of the Solutions:
(a) [tex]\(\log _8 5-\log _8 11=\log _8 \left(\frac{5}{11}\right)\)[/tex]
(b) [tex]\(\log _7 3+\log _7 11=\log _7 33\)[/tex]
(c) [tex]\(\log _7 \frac{1}{25}=-2 \log _7 5\)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.